Essential and non-essential element concentrations in two sleeper shark species collected in arctic waters - McMeans, Bailey C.; Borgå, Katrine; Bechtol, William R.; Higginbotham, David; Fisk, Aaron T. (Environmental Pollution, 2007)
A number of elements/metals have increased in arctic biota and are of concern due to their potential toxicity. Most studies on elements in the Arctic have focused on marine mammals and seabirds, but concentrations in the Greenland shark (Somniosus microcephalus) and Pacific sleeper shark (Somniosus pacificus), the only two shark species known to regularly inhabit arctic waters, have never been reported. To address this data gap, concentrations and patterns of 25 elements were analyzed in liver of Greenland sharks collected about Cumberland Sound (n = 24) and Pacific sleeper sharks collected about Prince William Sound (n = 14). Several non-essential elements differed between species/locations, which could suggest geographical exposure differences or ecological (e.g., diet) differences between the species. Certain essential elements also differed between the two sleeper sharks, which may indicate different physiological requirements between these closely related shark species, although information on such relationships are lacking for sharks and fish. © 2006 Elsevier Ltd. All rights reserved.